Latviešu literatūras procesi un personības (2008)
Mit engl. Zusammenfass.
PT: Processes and personalities of Latvian literature
Keywords: Konferenzschrift; Language and literature; Language. Linguistic theory. Comparative grammar; Philology. Linguistics; Literatur; Lettisch